Role of genotypes selected for minimum and maximum inflammatory reactivity in the response to the implantation of biomaterials (Ti) and in the osseointegration process in mice - Melchiades, Jessica Lima (2024)
Studies suggest that the inflammatory immune response, as long as it presents a controlled and self-limited profile, is important in the repair and osseointegration process, possibly contributing as a mediator of chemoattraction, activation, and differentiation of different cell types involved in repair. Among the different cell types recruited during the response, macrophages are also considered important elements in the repair and osseointegration process. Although classically considered proinflammatory cells, macrophages can present distinct functional phenotypes, called M1 (considered pro-inflammatory) and M2 (anti-inflammatory and/or pro-reparative). As for tissue repair, it is believed that M1 macrophages predominate in the initial phases and contribute to the initiation of the \'constructive inflammation\' process, which enables cell migration to the repair site, contributing to removing necrotic/damaged tissues, followed by the transition for the subsequent predominance of M2 cells, which would constitute an important source of growth factors at the repair site. On the contrary, responses of a chronic and exacerbated nature, characterized by an uncontrolled balance between pro- and anti-inflammatory mediators, in theory, have a deleterious effect on the repair and osseointegration process. In this context, the use of mouse strains with distinct inflammatory phenotypes has proven to be an extremely useful experimental tool in studying the influence of the immune and inflammatory response in different models. Mouse lines genetically selected for maximum or minimum inflammatory response were developed through bidirectional selective breeding, giving rise to the AIRmax and AIRmin lines; so named for their maximum (max) or minimum (min) acute inflammatory response (AIR). The Slc11a1 gene was identified as one of those responsible for the differential response of such strains, accounting for the hyperresponsiveness of the AIRmax strain (R allele) and the low responsiveness of the AIRmin strain (S allele). Although the exact mechanisms by which Slc11a1 regulates the inflammatory immune response remain poorly understood, studies suggest that its action is derived from the control regulation of the flow of Fe ions, which in turn modulate the function/polarization of macrophages. Considering the scarcity of information in the literature regarding the influence of the immune and inflammatory response on the osseointegration/repair process associated with biomaterials, this project aims to determine the characteristics of the immune/inflammatory response of mice of the AIRmin and AIRmax lineages after the implantation of Ti devices (Ti screw in the maxilla, osseointegration model; Ti disc in the subcutaneous tissue, model of immune/inflammatory response and repair), and their impact on the osseointegration/repair process. Furthermore, after characterizing the response and osseointegration/repair phenotypes of the AIRmin and AIRmax lineages and characterizing the inflammatory immune response (with a main focus on M1/M2 polarization), we will use polarization targeting strategies to reverse the unfavorable phenotype and enhance the favorable phenotype, seeking to enhance osseointegration. Specifically, we used the AIRmin and AIRmax lineages in models of osseointegration (implantation of a Ti screw in the maxilla) and immune/inflammatory response and repair (implantation of a Ti disc in the subcutaneous tissue), with these models being evaluated using microtomography and histological analyzes (histomorphometry and immunohistochemistry), as well as molecular analysis using the PCR Array, validated by ELISA. It is believed that the joint analysis will contribute to clarifying the magnitude and nature of the immune/inflammatory process and the response to biomaterials, and its impact on the subsequent osseointegration and repair processes.